Early findings from the integration of hypertension care into differentiated service delivery models for HIV in Uganda: a mixed‐method study - John Baptist Kiggundu; Fred C. Semitala; Chelsea Faith Lipoto; Lilian Giibwa; Robert Twine; Savio Mwaka; Florence Ayebare; Christine Kiwala; Evelyn N. Magambo; Gerald Mutungi; Isaac Ssinabulya; Donna Spiegelman; et al. (Journal of the International AIDS Society)
Abstract Introduction Uganda's national guidelines recommend integrated HIV and hypertension care; however, integration of hypertension care into HIV differentiated service delivery (DSD) models has not been extensively described. We aimed to describe trends in DSD models for people living with HIV (PLHIV) with hypertension and to qualitatively describe the experiences of healthcare providers (HCPs) and PLHIV with hypertension after implementing integrated care. Methods We conducted a parallel convergent mixed methods study nested in an ongoing stepped wedge cluster randomised trial in Kampala and Wakiso districts. Quantitative data (age, sex, blood pressure, DSD model, medication prescriptions) were collected from routine medical records at eight clinics implementing the enhanced care package between March 2023 and July 2024. Additionally, structured interviews were conducted at two clinics with HCPs (n = 6, 3 per clinic) and PLHIV with hypertension (n = 8, 4 per clinic). Our quantitative outcome variable was enrolment in intensive DSD models (facility‐based individual and group models) versus other DSDs. A generalised estimation equation was used to account for within clinic correlation and repeated measures within participants over time. Inductive thematic analysis was applied to the qualitative data using the Consolidated Framework for Implementation Research. Results Overall, 3164 PLHIV with hypertension accessed care at the eight clinics. Median age was 46 years (IQR 38–56); more than two‐thirds were female. There was considerable heterogeneity across clinics in the use of DSD models during the study period. Overall, use of intensive models increased over time (OR 1.127 [1.059−1.199] per month). However, two clinics showed significant time interaction effects (Wald test χ2 (7) = 69.94, p < 0.001), with a decrease in the intensive models over time. HCPs and PLHIV observed that integrating hypertension care was easily adaptable in some models, while more challenging in others. The availability of resources and synchronisation of HIV and hypertension visits facilitated the integration of hypertension care within the HIV DSD models. Conclusions The integration of hypertension management into HIV DSD models is both feasible and adaptable; however, it requires transitioning PLHIV between various models based on clinical needs. To facilitate this process, comprehensive client education by the HCPs is necessary. Clinical Trial Number clinicaltrials.gov # NCT05609513